Luminescent nanohybrids based on silica and silylated Ru(II)-Yb(III) heterobinuclear complex: new tools for biological media analysis - Sabio, Rafael Miguel [UNESP] (2020)
Lanthanide (Ln) complexes emitting in the near-infrared (NIR) region have fostered great interest as upcoming optical tags owing to their high spatial and temporal resolution emission as well deeper light penetration in biological tissues for non-invasive monitoring. For use in live-cell imaging, lanthanide complexes with long-wavelength absorption and good brightness are especially critical. Light-harvesting ligands of Ln complexes are typically excited in the ultraviolet region, which in turn trigger simultaneously autofluorescence and long-exposition damage of living systems. The association of d-metalloligands rather than organic chromophores enables the excitation of NIR-emitting Ln complex occurs in the visible region. Taking advantage of the long-lived excited states and intense absorption band in the ultraviolet (UV) to NIR region of Ru(II), we successfully design a dual-emitting (in the visible and NIR region) d-f heterobinuclear complex based on Ru(II) metalloligand and Yb(III) complex. In addition, we developed luminescent nanohybrids by grafting of Ru(II)-Yb(III) heterobinuclear complexes containing silylated ligands on the surface of mesoporous and dense silica matrix. The nanomarkers were successfully applied for imaging of murine melanoma B16-F10 and neonatal human dermal fibroblast HDFn cell cultures by one-photon or two-photon absorption using laser scanning confocal microscopy. Great cellular uptake, low cytotoxicity and the possibility to achieve visible and NIR emission via two-photons excitation show that the nanohybrids are remarkable markers for in vitro and a potential tool for in vivo applications.